The role of the mother tongue in EFL classrooms: Kurdish learners’ experiences and teachers’ perspectives - Zanyar Nathir Ghafar; Omar Mohammad-Ameen Ahmad Hazaymeh; Bareq Raad Raheem (Yayasan Mitra Persada Nusantara, 2026)
This study explores the role of the mother tongue in English language classrooms by examining the experiences of Kurdish learners and the perspectives of their teachers at Gasha Educational Community. It investigates why students use Kurdish during English lessons and how this practice affects learning outcomes. A qualitative design was employed using semi-structured interviews with 16 students (Grades 4–7) and three English teachers. Findings indicate that Kurdish aids comprehension, reduces anxiety, and reinforces cultural identity, yet over-reliance may limit English proficiency. Both learners and teachers emphasised the importance of a balanced approach, where Kurdish scaffolds learning while English remains the primary instructional language. The study highlights the value of culturally responsive pedagogies that recognise learners’ linguistic backgrounds and enhance effectiveness in EFL classrooms.